Comportamento físico e avaliação microestrutural de argamassas produzidas a partir da mistura exaurida gerada na indústria de magnésio metálico - Carlos Augusto de Souza Oliveira (2004)
Mortars are among the most used materials in the field of building construction. Since two thousands years ago, the mortars have been used to pave buildings as well as to agglutinate bricks in walls. Its highly complex physical and chemical structure varies with parameters such as time, humidity and temperature. As a consequence, the study and analysis of mortars using the approach of Materials Science and Engineering is hardly carried out. In its production, it is usual the mixture with Portland cement. Portland Cement is a material with high hydraulic reactivity and its production is very expensive and makes the production of mortars expensive too. Actually, various by-product industrial processes have been researched with the goal of replacing partly or totally the Portland cement. In this way, the magnesium slag is by-product of metallic magnesium manufacturing which can be studied aiming the creation of new materials for building construction and to help resolving ecological problems due to its disposal. Since the knowledge on the influence of metallic magnesium slag on mortars reology is unknown,this research presents the goal of studying how the addition of metallic magnesium slag influences physical and chemical properties, as well as the microstructural evolution of the traditional mortars used in building construction when Portland cement is replaced by magnesium slag. The characterization of the magnesium slag showed the predominant presence of dolomite and calcium silicates, however these silicates were found in the polymorphic form gC2S that is not reactive. DRX analyses showed the presence of free CaO and MgO in the periclase form, which are considered causing agents of expansion in mortars and hardened concrete. As mineral addition in the manufacture of mortars, of themechanical point of view, mortars composed of magnesium slag presented a decrease of compressive strength and tensile strenght under flexion, proportional to the magnesium slag used in its manufacture, being the decrease in resistance, related to the mineralspresent in this by-product.